Research on the Model of Public Physical Teaching in Universities in the Context of Modern Information Technology - Tian, Jiageng (Transactions on Social Science, Education and Humanities Research, 2024)
With the advent of the information and network era, new opportunities have emerged for the development of educational and teaching work. In the context of public physical teaching in universities, the rational application of modern information technology based on actual development situations plays a significant role. It can enrich teaching methods, improve teaching efficiency, meet students’ diverse learning experiences, and ensure the quality and efficiency of teaching. However, due to objective factors, there are still some problems in the actual application process, such as the limited ability of some teachers to use information technology and the lack of investment in teaching resources, which directly limit the advantages of information technology and even affect the final teaching effectiveness, leading to counterproductive effects. Therefore, in the future development, it is necessary to strengthen the information technology training for teachers, improve their application ability and information literacy, so that they can better integrate modern information technology with physical teaching. When conditions permit, increase the investment in information technology, improve infrastructure construction, and provide necessary hardware support for public physical teaching in universities.